Production preference barriers and lowland-appropriate strategies of sustaining local food systems in drought-affected southern Ethiopia - Thomas Toma Tora (Discover Sustainability, 2024)
Abstract A key element of food systems that look for significant inputs to ensure food security is food production. The production process is adversely affected by impermanent climates, particularly in places where droughts occur recurrently. In southern Ethiopia’s drought-prone Gamo lowlands, this study explores lowland-friendly strategies and challenges to food production choices. A cross-sectional survey design centered on households was utilized. Primary and secondary sources of data were used in the data collection process. The study’s primary data sources were the survey participants. The main methods used for gathering data were field observations, key informant interviews, focus group discussions, and surveys. Both qualitative and quantitative methods were employed in the data analysis. Numerous obstacles stand in the way of food production preference, according to the results of the household-level study. The most often mentioned ones were low professional support, rising production input costs, inadequate professional support, and traditional agriculture methods. The methods that were found included improving access to basic production resources like farmland and oxen as well as managing production costs to a reasonable level in order to alleviate these constraints. Furthermore, it was discovered that reevaluating the trends in production that are transitioning from food crops to cash crops is a major problem in the Gamo lowland environment. With growers paying less attention to valuable food sources—root crops in particular—the move toward cash crops is one that should be closely monitored. As a result, it is advised that local food systems need to be sustainable in view of changing climate and a growing populace.